Impaired antioxidant capacity causes a disruption of metabolic homeostasis in sickle erythrocytes - Chaves, Nayara Alves [UNESP]; Alegria, Thiago Geronimo Pires; Dantas, Lucas Souza; Netto, Luis Eduardo Soares; Miyamoto, Sayuri; Bonini Domingos, Claudia Regina [UNESP]; da Silva, Danilo Grünig Humberto [UNESP] (My University, 2019)
This study examined particularly relevant redox pathways such as glycolysis, pentose phosphate pathway (PPP), metHb reductase and nucleotide metabolism, in order to better address how sickle cells deal with redox metabolism disruption. We also investigated the generation of specific oxidative lesions, and the levels of an unexplored antioxidant that could act as a candidate biomarker for oxidative status in sickle cell anemia (SCA). We adopted rigorous exclusion criteria to obtain the studied groups, which were composed by 10 subjects without hemoglobinopathies and 10 SCA patients. We confirmed that sickle cells overwhelm the antioxidant defense system, leading to an impaired antioxidant capacity that significantly contributed to the increase in cholesterol oxidation (ChAld) and hemolysis. Among the antioxidants evaluated, ergothioneine levels decreased in SCA (two-fold). We found strong correlations of ergothioneine levels with other erythrocyte metabolism markers, suggesting its use as an antioxidant therapy alternative for SCA treatment. Moreover, we found higher activities of MetHb reductase, AChE, G6PDH, HXK, and LDH, as well as levels of NADPH, ATP and hypoxanthine in sickle cells. On this basis, we conclude that impaired antioxidant capacity leaves to a loss of glycolysis and PPP shifting mechanism control and further homeostasis rupture, contributing to a decreased lifespan of sickle cells.
Keywords: Acetylcholinesterase; Ergothioneine; Metabolic homeostasis; Oxysterols